Protein trafficking in neurons - Bean, Andrew J. (Elsevier/Academic Press, 2007)
The efficient delivery of cellular constituents to their proper location is of fundamental importance for all cells and is of particular interest to neuroscientists, because of the unique functions and complex architecture of neurons. Protein Trafficking in Neurons examines mechanisms of protein trafficking and the role of trafficking in neuronal functioning from development to plasticity to disease. The book is divided into seven sections that review mechanisms of protein transport, the role of protein trafficking in synapse formation, exo- and endocytosis, transport of receptors, trafficking of ion channels and transporters, comparison of trafficking mechanisms in neuronal vs. non-neuronal cell types, and the relationship between trafficking and neuronal diseases such as Alzheimer's, Huntington's and Prion Diseases. Provides a comprehensive examination of membrane/protein movement in neuronal function. Sections on synapse development, synaptic transmission, and the role of trafficking in neurological disease Includes a focus on Molecular Mechanisms Illustrated with color summary pictures The only book examining protein trafficking and its functional implications, written by leaders in the field.